PENGELOLAAN FASILITAS PADA KAWASAN WISATA ZIARAH MAKAM SYEKH ABDURRAHMAN SIDDIQ DI SAPAT KABUPATEN INDRAGIRI HILIR - Veni Basoja Khomuna; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The facility is a component that can support the course of activities in a tourist destination. This research was conducted at the Tomb of Syekh Abdurrahman Siddiq located in Teluk Dalam Parit Hidayat Village, Sapat, Kuala Indragiri, Indragiri Hilir Regency. The tomb of Syekh Abdurrahman Siddiq was the Tomb of the first Mufti of the Indragiri Kingdom during the reign of Sultan Mahmud Syah based in Rengat. This tomb is one of the pilgrimage attractions that have been established by the Indragiri Hilir Regency Government. The facilities contained in the Tomb of Syekh Abdurrahman Siddiq consist of the main facilities, supporting facilities and complement facilities where all three must be fulfilled in order to create a good tourist destination. This study aims to find out how to manage the facilities at the Tomb of Syekh Abdurrahman Siddiq. Data of this rearch was obatained from observation, interviews, and documentation, with data collection techniques using key informant purposive sampling. This study describes the general description of Syekh Abdurrahman Siddiq's Tomb Pilgrimage Tourism Area and how to manage the facilities at the Tomb of Syekh Abdurrahman Siddiq starting from the main facilities, supporting facilities to complement facilities.Keywords: Management, Facilities, Pilgrimage, Tomb